Comparison of Intraocular Pressure after Phacoemulsification Compared to Laser Peripheral Iridotomy (LPI) in Acute Primary Angle Closure (APAC) Patients: A Systematic Review - Aulia Zinedinita Rahmasari, -
Abstract:Aim: To compare IOP in APAC patients after phacoemulsification compared to LPI.Background: Acute primary angle closure (APAC) is a type of PACG and an important cause of blindness in East Asia. In APAC patients, both LPI and phacoemulsification have been shown to be effective in controlling elevated IOP. Knowledge and information about changes in IOP after phacoemulsification and LPIin APAC patients, which is one of the criteria for successful APAC management, can be a reference as well as a consideration for choosing an effective treatment for APAC patients.Results: Of the 15 articles reviewed, 84% of patients who received phacoemulsification intervention experienced >50% reduction and 24.3% of patients experienced <50% decrease in post-op IOP compared with the mean pre-op IOP. While patients who received LPI intervention, 80.5% of patients experienced >50% reduction in IOP and 19.4% of patients experienced <50% reduction in IOP post-op compared with the mean pre-op IOP.Conclusion: There were decreases in IOP of APAC patients after phacoemulsification or LPI. In addition, there are differences in the decrease in IOP of APAC patients after phacoemulsification compared to LPI.Clinical Significance: Phacoemulsification and LPI are effective forlowering IOP in the early stages of an acute attack. LPIis the preferred procedure according to most guidelinesbecause it is relatively non-invasive, easy to administer on an outpatient basis, and has a lower risk of complications. Phacoemulsificatinhas been shown to be a more effective treatment than LPI for IOP reduction in early and medium-term IOP controls.